The Impact of the Free Visiting Hours Policy on Patient Satisfaction: Management Strategies for Ensuring Security, Infection Prevention, and Smooth Clinical Services (Case Study at PANTI RAHAYU Hospital Purwodadi) - Mara, Lusa; Teguh, Daniel; Hapsari, Pamungkas; Ardoko, Prono (Indonesian Journal Economic Review (IJER), 2025)
The intense competition in the healthcare services industry has pushed hospitals to adopt patient-centered care strategies, one of which is the implementation of a free visiting hours policy. This study aims to (1) analyze the effect of the free visiting hours policy on patient satisfaction levels, and (2) formulate a strategic managerial model to balance this flexibility with fundamental operational pillars: security, Infection Prevention and Control (IPC), and smooth clinical services. Using a quantitative approach with a cross-sectional survey design, data was collected from 120 non-ICU inpatients at PANTI RAHAYU Hospital Purwodadi through purposive sampling. The visiting hours policy variable was measured through perceptions of flexibility and family support, while patient satisfaction was assessed using the five dimensions of service quality (SERVQUAL). Pearson’s Correlation analysis showed a positive, strong, and highly significant relationship (r = 0.715; p < 0.01) between positive perceptions of free visiting hours and overall patient satisfaction. The highest satisfaction dimension was found in Empathy (mean = 4.45), emphasizing that this policy effectively meets patients' psychosocial needs. However, observations and slightly lower scores in the Reliability dimension (mean = 4.05) indicate a potential "managerial paradox," where this marketing asset may risk disrupting clinical workflows. As a solution, this study proposes the "Guided Flexibility" model, a framework that integrates proactive visitor education, the implementation of a Visitor Management System, setting "Priority Service Times," and empowering staff through assertive communication to ensure clinical services, security, and IPC standards are maintained without compromising patient satisfaction.